Simon Cowell’s Compliments in American Idol, Season 8, Episode 1 - Yuki Yoremasa Andrea (Institute of Research and Community Outreach - Petra Christian University, 2026)
This study examines the types and characteristics of compliments used by Simon Cowell in American Idol, Season 8, Episode 1. The study is based on the idea that compliments functioned not only to give a positive evaluation but also play an important role in media communication. This study aims to answer two research questions. Using a qualitative approach, all the data were collected from one specific YouTube video, including the whole video’s transcript, then analyzed using a theory of compliments by Alfonzetti (2013). Although Simon Cowell is recognized for his harsh criticism, this study focuses only on how he delivers compliments that shape society’s perception. The way he compliments the contestant has made his compliments more memorable and motivated the contestants. The study reveals that Simon Cowell uses both explicit and implicit compliments and demonstrates all five characteristics of compliments proposed by Alfonzetti (2013).